2022
DOI: 10.3390/jcm11175209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Home-Based Transcranial Direct Current Stimulation on Experimental Pain Sensitivity in Older Adults with Knee Osteoarthritis: A Randomized, Sham-Controlled Clinical Trial

Abstract: Although transcranial direct current stimulation (tDCS) is encouraging regarding clinical pain intensity for individuals with knee osteoarthritis, very few studies have explored its impact on experimental pain sensitivity, which may hinder our understanding of underlying therapeutic mechanisms. The purpose of this study was to assess the efficacy of 15 home-based tDCS sessions on experimental pain sensitivity and explore its relationships with clinical pain intensity. We randomly assigned 120 participants to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our findings also suggest that the chronic pain experienced by individuals with ADRD involves central processing mechanisms since tDCS was able to impact pain intensity. Indeed, tDCS is a neuromodulation method potentially affecting pain processing pathways as shown in our studies using neuroimaging and conditioned pain modulation (CPM) measures [ 48 , 80 , 81 , 82 ]. We found significant changes in hemodynamic brain activity measured with functional near-infrared spectroscopy (fNIRS) [ 80 , 81 , 82 ], and simultaneously observed a significant increase in CPM in the active group as opposed to the sham group after tDCS [ 48 ], which coincides with tDCS studies using functional magnetic resonance imaging (fMRI) in both healthy subjects [ 83 , 84 ] and chronic pain patients [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings also suggest that the chronic pain experienced by individuals with ADRD involves central processing mechanisms since tDCS was able to impact pain intensity. Indeed, tDCS is a neuromodulation method potentially affecting pain processing pathways as shown in our studies using neuroimaging and conditioned pain modulation (CPM) measures [ 48 , 80 , 81 , 82 ]. We found significant changes in hemodynamic brain activity measured with functional near-infrared spectroscopy (fNIRS) [ 80 , 81 , 82 ], and simultaneously observed a significant increase in CPM in the active group as opposed to the sham group after tDCS [ 48 ], which coincides with tDCS studies using functional magnetic resonance imaging (fMRI) in both healthy subjects [ 83 , 84 ] and chronic pain patients [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tDCS is a neuromodulation method potentially affecting pain processing pathways as shown in our studies using neuroimaging and conditioned pain modulation (CPM) measures [ 48 , 80 , 81 , 82 ]. We found significant changes in hemodynamic brain activity measured with functional near-infrared spectroscopy (fNIRS) [ 80 , 81 , 82 ], and simultaneously observed a significant increase in CPM in the active group as opposed to the sham group after tDCS [ 48 ], which coincides with tDCS studies using functional magnetic resonance imaging (fMRI) in both healthy subjects [ 83 , 84 ] and chronic pain patients [ 85 , 86 ]. In relation to ADRD, recent evidence suggests that there might be a link between pathological processes of ADRD and chronic pain [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our research has previously shown that tDCS has a beneficial effect on clinical subjective measures of pain in knee OA patients, 10 as well as experimental pain sensitivity. 11,12 We reported the efficacy of home-based tDCS treatment on experimental pain sensitivity measures such as the heat pain threshold (HPTh), heat pain tolerance (HPTo), pressure pain threshold (PPT), and conditioned pain modulation (CPM), as well as its relationship with clinical pain intensity measures such as the numeric rating scale (NRS) and Western Ontario and McMaster Universities Osteoarthritis Index. Changes in NPTh, NPTo, PPT, CPM, and NRS between the active and sham groups were found to be statistically significant after the third week of treatment 12 and 3 months from the baseline.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study assessing changes in neural connections assessed using fNIRS between cohorts that underwent home-based, self-administered tDCS treatment versus sham tDCS for several weeks, and it pairs with other reports from our group focused on clinical outcomes. 10,[12][13][14][15][41][42][43] 2 Materials and Methods…”
Section: Introductionmentioning
confidence: 99%